Design And Build Virtual Reality Technology To Create a 3D House Proprety simulation Based On Android - Supriyadi, Dede; Nurfaizal, Habib (Jurnal Informatika Universitas Pamulang, 2023)
Virtual realty is a technology that can make users feel like they are in a virtual world (virtual). This technology can be used in various fields such as marketing for housing. Currently, the marketing process is still a lot that uses brochures and mock-up forms or miniature model houses with the aim of promoting where visitors or potential home buyers can find out examples of houses offered. In addition to the standard usage of brochures by marketers, making this mock-up takes a relatively long time and the results of the mock-up are not very detailed and not as similar to the original house. From the results of existing data and information, it is necessary to evaluate to change the way of promotion in accordance with current technological advances which aims to make it easier for marketing parties to convey the products sold to prospective buyers, so as to make potential buyers interested in buying the house offered. This study designs a simulation using visualization with designs and concepts that make potential buyers feel the sensation of being in a marketed house. For system design used is using UML, namely the use of use case diagrams, and flowchart diagrams. This Virtual Reality application is made using the C programming language and for implementation using Unity and several other supporting tools such as Google VR SDK, Android Studio and Blender for modular design. It is hoped that this solution will be useful to make it easier to carry out promotions so that it attracts the interest of potential home buyers.